The effect of leaf extract supplementation on exercise-induced muscle damage and muscular performance: A systematic review and meta-analysis. Issue 17 (2nd September 2021) - Doma, Kenji; Gahreman, Daniel; Ramachandran, Akhilesh Kumar; Singh, Utkarsh; Connor, Jonathan
ABSTRACT: This systematic review and meta-analysis investigated the effects of leaf-plant extracts typically used for tea beverages on the level of exercise-induced muscle damage. The meta-analysis was conducted by comparing measures between the leaf-extract supplements (SUPP) and placebo (PLA) conditions at 24 h and 48 h following the muscle-damaging protocols from 19 studies with 416 participants. The results showed that the SUPP condition exhibited significantly lower indirect muscle damage markers than the PLA condition at 24- and 48-h post-exercise (p < 0.05). Furthermore, oxidative stress markers were significantly lower for the SUPP condition than the PLA condition at 24-h post-exercise (p < 0.05), although not at 48-h post-exercise (p > 0.05). In addition, no differences were found for anti-oxidant status at 24- and 48-h post-exercise (p > 0.05) between conditions. Muscle performance measures significantly increased for the SUPP condition than the PLA condition at 24-h post-exercise (p < 0.05), but not at 48-h post-exercise (p > 0.05). These results demonstrate that leaf plant extracts reduces the level of various biomarkers indicative of exercise-induced stress, although its effect on anti-oxidant status remains equivocal. Nonetheless, leaf-plant extracts typically ingested as a tea beverage may be an effective recovery strategy following strenuous exercises.